Analisis Tingkat Partisipasi Masyarakat Dalam Perencanaan Pembangunan Desa Di Kabupatem Agam - Misrawati Misrawati; Asep Ajidin (STIE AMKOP, 2023)
This research examines the level of community participation in village development planning in Nagari Koto Baru, Baso District, Agam Regency. The study explores various factors that influence community participation and identifies both supportive and inhibiting factors. Data was collected through surveys and interviews with respondents representing diverse age groups, genders, education levels, occupations, and lengths of residence in the village. The findings indicate that community participation in village development planning is diverse, with active involvement observed in attending planning meetings, contributing ideas and opinions, and actively participating in the implementation and utilization of development outcomes. Factors such as awareness, access to information, open forums, trust in the government, easy access to meeting places, and adequate budget allocation support community participation. However, challenges such as lack of awareness, limited access to information, absence of open forums, and mistrust in the government hinder community participation. The study offers recommendations for the local government to promote and enhance community participation, including addressing the inhibiting factors. Furthermore, the community is encouraged to increase their awareness and engagement in the development planning process, utilizing the provided information by the government. Keywords: Tingkat, Partisipasi, Perencanaan Pembangunan Desa, Kabupaten Agam